The Influence of Health Education About Dental Health on The Attitudes of Parents in Maintaining the Dental Health of Preschool Children in Paud Lentera Alam Campurdarat Village, Tulungagung District - Nurhidayah; Suhartini; Dewi Retno Puspitosari (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
The children’s dental hygiene is an effort of parents to keep the children’s teeth healthy and run its functions normally. The hygienic teeth was clean and no porous. The dental care was important, since some dental problems caused by unclean teeth such as dental plaque, dental caries, gum infection and dental porous. So the health education is very important. The design of this research was comparative analysis with pe-pascates approach in a group (One-group pre-test post-test design), the population was all parents of PAUD Lentera Alam Campurdarat Villlage Tulungagung Sub District, 40 respondents were taken a samples by total sampling technique. The independent variable was the health education about dental hygiene and the dependent one was the parents’ behavior to care the pre-school children’s dental hygiene. The data was obtained from questionnaires, analyzed with “Willcoxon Signed Rank Test” with Mean value p < 0,05. The research result was 29 respondents (73%) had good behavior, and there was an effect of health education about dental hygiene towards the parents’ behavior to care the pre-school children’s dental hygiene, (Willcoxon Signed Rank Test, p value 0.000 < 0.05, and then H0 was rejected). The conclusion was the health education in this research could changes the respondent’s’ behavior to care the pre-school children’s dental hygiene at present and in the future.